Financial Performance Effectiveness of PT Bank Central Asia Tbk 2019–2022 - Rasni Hanipa Usemahu; Juliana Kesaulya; Albertus Lalaun (Yayasan Sembilan Pemuda Indonesia, 2026)
This study evaluates the financial performance of PT Bank Central Asia Tbk during 2019–2022, covering the pre-pandemic, pandemic, and early economic recovery periods. A descriptive quantitative design was applied using secondary data from audited annual financial statements published through the Indonesia Stock Exchange. Financial performance was assessed through three indicators: quick ratio (bank-specific liquidity), debt-to-asset ratio (funding structure), and return on assets (profitability). The average quick ratio was 28.59%, classified as healthy, though it declined consistently from 49.89% in 2019 to 14.02% in 2022, indicating weakening capacity to cover short-term obligations. The average debt-to-asset ratio reached 82.14%, remaining relatively stable and reflecting deposit-based funding common in banking. Return on assets averaged 2.82%, indicating very healthy profitability temporarily declining in 2020 due to pandemic pressures, but improving in 2021 and recovering strongly in 2022. This study provides an integrated time-series interpretation of liquidity, funding structure, and profitability, demonstrating that strong earnings recovery coexisted with declining immediate liquidity coverage and persistently high liabilities. The continued decline in the quick ratio highlights the need for careful liquidity management despite resilient profitability. This research contributes empirical evidence on banking resilience during crisis periods, offering actionable insights for management and regulators. Future studies should incorporate additional indicators, longer observation periods, and comparative analysis with other major Indonesian banks.